Technology shocks and hours worked: A cross-country analysis - Jacqueline Thomet; Philipp Wegmüller (University of Bern, Department of Economics, 2018)
Using a novel data set, we reassess the evidence for (or against) a key implication of the basic RBC model: that aggregate hours worked respond positively to a positive technology shock. Two novel aspects of the analysis are the scope (14 OECD countries) and the inclusion of data on both labor supply margins to analyze the key margin of adjustment in aggregate hours. We show that the short-run response of aggregate hours to a positive technology shock is remarkably similar across countries, with an impact fall in 13 out of 14 countries. In contrast, the decomposition of the aggregate hours results into intensive and extensive margins shows substantial heterogeneity in the labor market dynamics across OECD countries. For instance, movements in the intensive margin are the dominant channel of adjustment in aggregate hours in 5 out of 14 countries of our sample, including France and Japan.
Keywords: E24; E32; 330; Structural VAR; technology shocks; aggregate hours worked; labor supply margins; relative price of investment